Characterising thermal runaway within lithium-ion cells by inducing and monitoring internal short circuits. Issue 6 (29th March 2017) - Finegan, Donal P.; Darcy, Eric; Keyser, Matthew; Tjaden, Bernhard; Heenan, Thomas M. M.; Jervis, Rhodri; Bailey, Josh J.; Malik, Romeo; Vo, Nghia T.; Magdysyuk, Oxana V.; Atwood, Robert; Drakopoulos, Michael; et al.
Abstract : Internal short circuiting device for lithium-ion batteries. Abstract : Lithium-ion batteries are being used in increasingly demanding applications where safety and reliability are of utmost importance. Thermal runaway presents the greatest safety hazard, and needs to be fully understood in order to progress towards safer cell and battery designs. Here, we demonstrate the application of an internal short circuiting device for controlled, on-demand, initiation of thermal runaway. Through its use, the location and timing of thermal runaway initiation is pre-determined, allowing analysis of the nucleation and propagation of failure within 18 650 cells through the use of high-speed X-ray imaging at 2000 frames per second. The cause of unfavourable occurrences such as sidewall rupture, cell bursting, and cell-to-cell propagation within modules is elucidated, and steps towards improved safety of 18 650 cells and batteries are discussed.